ฐานอาคารสถาปัตยกรรมไทย - นิ่มเล็ก, สมใจ (NAJUA: Architecture, Design and Built Environment, 2016)
ฐานอาคารสถาปัตยกรรมไทย ทําหน้าที่เป็นโครงสร้าง และส่วนประดับตกแต่งอาคาร รูปแบบของฐานมีหลายรูปแบบถามแต่ละช่วงสมัยของสถาปัตยกรรมและแต่ละสายช่างแต่ละท้องถิ่น การเรียกชื่อฐานของอาคารยังเป็นไปตามลักษณะรูปแบบที่เกิดขึ้นด้วย Pedestals of Traditional Thai Architecture Pedestals of traditional Thai architecture serve as a part of the structure as well as a decorative element. There are many different designs depending on the period and schools according to each region, and each design has a specific name.